Dampak Kebijakan Kenaikan Harga Minyak Goreng Rakyat Terhadap Distributor di DKI Jakarta - Bentonius Silitonga (Eduturisma, 2024)
To overcome the problem of stability, certainty, and affordability of cooking oil prices, the government has issued regulations that regulate the trade process from upstream to downstream even though in reality the price in the market remains high and scarce. The study aims to examine the impact of the policy of increasing the price of cooking oil in terms of price stability and supply chain management felt by distributors in DKI Jakarta. The study uses qualitative methods through in-depth interview techniques. The results of the analysis use interview data, literature reviews, government reports, and other official websites. The results of the study revealed that government policy has not considered the domino effect of an uncertainty in the addition of export quotas that affect the Domestic Market Obligation on the availability of Minyakita. In addition, allegations of cooking oil cartel practices and speculator behavior are factors that hinder the implementation of the policy properly. As a conclusion of the study, the impact of the policy of increasing the price of cooking oil does not have a strong influence on price stability and supply chain availability, ambiguous trade, and the government's inability to oversee the business process from upstream to downstream.